Examining Monogamy Through the Lens of Jamaluddin Athiyyah's Maqashid Syariah - Ulum , Moh. Rafiqil; Hamidah , Tutik (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2024)
Monogamy, as a form of marriage between one man and one woman, is widely considered the ideal norm in many cultures as it is associated with stability, commitment, and fidelity. In the Islamic context, monogamy is preferred as it is considered more manageable and conducive to domestic harmony. However, Islam also allows polygamy under certain conditions, which has led to an ongoing scholarly debate regarding its ethical and practical implications. While there has been much discussion regarding monogamy and polygamy in Islam, there has been little research using a maqashid sharia approach, particularly from the perspective of Jamaluddin Athiyyah. This research seeks to do so by assessing how monogamy aligns with the objectives of Islamic law compared to polygamy. This research uses a normative qualitative method with a conceptual approach. Primary data is obtained from Jamaluddin Athiyyah's works on maqashid sharia, while secondary data includes relevant journals, articles, and previous research on monogamy and polygamy. The qualitative analysis evaluates the role of monogamy in fulfilling the values of maqashid sharia, particularly in the domains of personal well-being, family stability, community harmony, and overall human well-being. The findings show that monogamy is more supportive of justice, tranquility, and well-being in family life than polygamy. From the perspective of Jamaluddin Athiyyah's maqashid sharia, monogamy significantly contributes to preserving the soul, reason, religion, honor, and. In addition, monogamy enhances social stability and promotes the welfare of the ummah, which is in line with the basic objectives of Islamic law, which are to achieve prosperity and prevent societal breakdown. Therefore, these findings will be useful for Muslim policymakers, academics, and society in understanding monogamy as a marriage framework that is more supportive of social justice and welfare.